2016
DOI: 10.1364/boe.8.000078
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of hemodynamic and structural characteristics of in vivo brain tissue using total diffuse reflectance spectrum measured in a non-contact fashion

Abstract: Abstract:Here we present a new methodology that investigates the intrinsic structural and hemodynamic characteristics of in vivo brain tissue, in a non-contact fashion, and can be easily incorporated in an intra-operative environment. Within this methodology, relative total diffuse reflectance spectra (R TD (λ)) were acquired from targets using a hybrid spectroscopy imaging system. A spectral interpretation algorithm was subsequently applied to R TD (λ) to retrieve optical properties related to the composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…With this stochastic photon propagation method, the estimated optical power/photoresponse was calculated for different rStO 2 at two wavelengths. The absorption coefficients [μ a (λ)] as a function of rStO 2 are given by the following equation ( 52 , 53 )μafalse(normalλfalse)= ln10true(false[Hbfalse]tMWtrue(rStO2εHbO2false(normalλfalse)+false(1rStO2false)εHbfalse(normalλfalse)true)+italicWμWfalse(normalλfalse)true)where [Hb] t is the total concentration of hemoglobin, M W is the molecular weight of hemoglobin (64,500 g mol −1 ), W is the water content (%), and μ W (λ) is the absorption coefficient of water. The ε(λ) of HbO 2 and Hb, and μ W (λ) are available from ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With this stochastic photon propagation method, the estimated optical power/photoresponse was calculated for different rStO 2 at two wavelengths. The absorption coefficients [μ a (λ)] as a function of rStO 2 are given by the following equation ( 52 , 53 )μafalse(normalλfalse)= ln10true(false[Hbfalse]tMWtrue(rStO2εHbO2false(normalλfalse)+false(1rStO2false)εHbfalse(normalλfalse)true)+italicWμWfalse(normalλfalse)true)where [Hb] t is the total concentration of hemoglobin, M W is the molecular weight of hemoglobin (64,500 g mol −1 ), W is the water content (%), and μ W (λ) is the absorption coefficient of water. The ε(λ) of HbO 2 and Hb, and μ W (λ) are available from ( 27 ).…”
Section: Methodsmentioning
confidence: 99%
“…The scattering coefficient [μ s (λ)] at the dominant emission wavelength was calculated using the following equation ( 53 )μsfalse(normalλfalse)=italicatrue(falseλ500true)italicb1italicgwhere a is a scaling coefficient, b is the scattering power, and g is the anisotropy factor. For simulation in rodent’s brain ( a = 21.4 cm −1 and b = 1.2), the calculated μ s (540 nm) = 195.2 cm −1 ( g = 0.89) and μ s (625 nm) = 163.2 cm −1 ( g = 0.90).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spectral channel was selected because it presents one of the absorption peaks of hemoglobin in the HS image dataset employed in the experiments. Previous works have shown that the hemoglobin concentration absorption peak is normally found between 500–590 nm [ 48 , 49 , 50 ]. As it can be seen in Figure 3 , shows a high contrast between the brain tissue and the blood vessels, but the background (especially rubber ring markers) and the specular glare are indistinguishable from the blood vessels.…”
Section: Methodsmentioning
confidence: 99%